2008
DOI: 10.1097/prs.0b013e3181811ce8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Characterization of Orbital Changes with Age and Associated Contributions to Lower Eyelid Prominence

Abstract: The authors' measurements suggest that with aging there is a significant increase in anterior inferior periocular soft-tissue volume, and that fat expansion is the main contributor to this volume increase. These observations provide supporting evidence that orbital fat expansion occurs with age and is the primary age-associated contributor to lower eyelid prominence, rather than globe descent or fat repositioning caused by weakening of the orbital septum. We believe these data suggest that fat excision should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 7 publications
3
30
3
3
Order By: Relevance
“…The significant correlation of age with TOFV may be attributable to a relative reduction in muscular bulk and volume of the globe itself with increasing age (23,24). In addition, Darcy et al (25) observed an increase in total orbital fat and periocular soft tissue with aging, which they claimed was due to fat expansion, which is consistent with the results of the present study, and which may be the rationale for fat excision from the eyelids in plastic and aesthetic surgery. Although the present study revealed an increase in TOFV and TOV with respect to age, there was no statistically significant correlation between the changes in TOFV and TOV, which should be further investigated.…”
Section: Unstandardized Coefficients --------------------------------supporting
confidence: 81%
“…The significant correlation of age with TOFV may be attributable to a relative reduction in muscular bulk and volume of the globe itself with increasing age (23,24). In addition, Darcy et al (25) observed an increase in total orbital fat and periocular soft tissue with aging, which they claimed was due to fat expansion, which is consistent with the results of the present study, and which may be the rationale for fat excision from the eyelids in plastic and aesthetic surgery. Although the present study revealed an increase in TOFV and TOV with respect to age, there was no statistically significant correlation between the changes in TOFV and TOV, which should be further investigated.…”
Section: Unstandardized Coefficients --------------------------------supporting
confidence: 81%
“…[6][7][8][9][10][11][12]23 Other studies have examined age-related volumetric changes in the facial soft tissue and described an increase in the orbital fat and lower eyelid fat, as well as selective atrophy in the cheek fat associated with increasing patient age. 1,[24][25][26][27] While prior studies have described the repositioning of facial soft tissues and the volume changes in the facial fat as primary contributors to the appearance of an older face, it is also possible that specific, age-related changes in facial tissue properties also contribute to the findings associated with an older appearing face.…”
Section: Introductionmentioning
confidence: 79%
“…The age-related increases in T2 values, accompanied by increases in T1 values particularly in male subjects, are suggestive of increasing water content, which may be associated with unique properties of the orbit as previously described. 26 Those qMRI characteristics would help in designing anti-ageing strategies specifically for eye regions.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the vertical distance from the muscle belly to the electrode, we compared data from several papers. The vertical distance from the inferior aspect of the globe to the orbital floor is about 7 mm (Darcy et al, 2008;Stephan et al, 2009). The IO muscle thickness at the point where it crosses the inferior rectus insertion is about 2.5 mm (Kaufmann and Steffen, 2004).…”
Section: Appendix Amentioning
confidence: 99%